ZnO-SiO₂ Nanocomposite: Synthesis, Characterization, and Application of Corrosion Inhibition - Alam Q. AL-Hussin; Taleb Bader, Ali; Al-Gubury, Hazim Yahya (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Herein, we are reporting the synthesis of zinc oxide (ZnO), silicon dioxide (SiO2), and a binary nanocomposite ZnO-SiO2 by the co-precipitation method. The materials were comprehensively characterized, such as via Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), powder X-ray diffraction (XRD), UV–Vis spectroscopy, and nitrogen adsorption–desorption (BET) measurements before their application. The presence of typical Zn-O and Si-O vibrations characteristic of ZnO was confirmed by FTIR spectra, whereas the hexagonal morphology of ZnO crystals, spherical SiO2, and agglomerated ZnO-SiO2 nanostructures were confirmed by SEM images. XRD measurements showed the crystallinity of the as-obtained nanostructures and the average crystallite sizes of 37.78 nm for ZnO, 48.01 nm for SiO2, and 34.09 nm for composite ZnO-SiO2 as determined by the Scherrer equation. The synthesized ZnO, SiO2, and ZnO-SiO2 nanoparticles were then evaluated on the basis of their inhibitive abilities toward corrosion processes in mild steel coupons exposed to 1M HCl estimated by potentiodynamic polarization. All the studied binary composites emerged as having the strongest inhibitory potential, with the ZnO-SiO2 nanocomposite root system experience showing the most powerful inhibition potential, reducing the corrosion current density i-corr to 36.1 µA cm-2 and reaching 93% inhibition efficiency. These results demonstrate that the future of using co-precipitation-based synthesis lies in the ability to obtain tunable nanostructure composites with desirable physicochemical properties and efficient corrosion inhibition in acidic media